Theresa May et l’échec du « meaningful vote » : approche argumentative - Alma-Pierre Bonnet (Anglophonia)
As soon as she reached power, Theresa May said that she wanted to respect the will of the British people to leave the European Union (EU). She took a firm stance concerning Europe so as to please the right wing of her party, the Tories, reinforce her credibility and preserve the unity of her party. She triggered Article 50 without trying to find any form of compromise with any other party beforehand. In the meantime, the government agreed to put any EU/ UK deal to the vote in Westminster (the so-called “meaningful vote”). At the end of tough negotiations, May had therefore to convince Parliament that the deal she had struck with the EU respected the will of the British people and guaranteed Britain’s economic and diplomatic continuity. After three crushing defeats, May was forced to resign. The present article will study this perilous endeavour through a corpus-based analysis of Theresa May’s declarations (speeches, addresses, letter to the nation) to understand the reasons behind this failure. Ruth Amossy’s book, L’argumentation dans le discours, will be used as the basis of our research. We will try to explain why the arguments used by May failed to convince MPs.